Capacity Gaps in Local Flood Risk Governance: Policy Challenges in the City of Makassar - Iskandar, Didik (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
This study aims to analyze the capacity gaps in flood risk governance in Makassar City. Using a quantitative approach with a survey method, this study involved 120 respondents from relevant local government agencies. The research instrument was a Likert-based questionnaire, which was compiled based on three dimensions of policy capacity: analytical, institutional, and political capacity. The results of multiple linear regression analysis showed that the three variables had a significant effect on the effectiveness of flood governance, with institutional capacity as the most dominant factor. Analytical capacity also contributed significantly to supporting data-based planning, while political capacity showed the lowest influence due to weak cross-period support and minimal public participation. These findings indicate that the effectiveness of flood policies depends on cross-sector synergy and consistent political support. Therefore, strengthening institutional capacity, integrating data between agencies, and increasing public policy literacy are key to building adaptive and sustainable flood governance amidst the pressures of urbanization and climate change